MANAGEMENT ACTIVITY OF IP LVOV IN THE POSITION OF HEAD OF THE DEPARTMENT OF PEDAGOGY OF THE CHERNIGIV PEDAGOGICAL INSTITUTE (1952–1958) - А. Остапенко (Київський національний університет імені Тараса Шевченка, 2020)
The article shows I. P. Lvov, сhairman of the Department for pedagogy of Chernihiv Pedagogical Institute.I. P. Lvov worked as the Head of the Department of Pedagogy from 1952 to 1958. He developed didactic materials on pedagogy, logic and psychology. The curriculum for the second semester was analyzed, where the main tasks were students' educational work, advanced training of teachers and realization of рublic works under the teachers.At the faculty meeting, the lecturers approved the Individual work plans of the members of the department, monitoring the lectures and pedagogical lessons from the point of view of scientific and methodological execution, control over the work of a laboratory assistant, review and approval of the work plan of pedagogical practice of students.I. P. Lviv had intended to purchase a separate room for conducting psychological experiments. Unfortunately, the intention failed for unknown reasons. He controlled the quality of lectures and seminars on pedagogy, lectures on psychology, and reported on the visit by the directorate of the institute and individual members of the chair they reviewed.In 1952, a pedagogical circle was formed at the department of pedagogy. I. P. Lviv was group leader of the circle at one of the meetings read a report "Modern problems of restructuring the science of psychology in the academician I. P. Pavlov".I. P. Lviv appreciated the work of the laboratory assistant of the department of G. P. Svirid, pointing to her faithful discharge of her duties: providing students with educational and recommended literature.The content of the documents of I. P. Lvov on an administrative post was analyzed and he was found that he made some comments in the report at the meeting of the pedagogy department of the Chernihiv Pedagogical Institute, as well as at the meeting of the Institute council concerning the issues that were in the report "On the condition of pedagogical science and eliminating its backlog" on the resolution of I. A. Kairov.In 1955 I. P. Lvov was the head of the commission on State examinations of the correspondence department of the Russian language and literature of the Chernihiv Pedagogical Institute. Analysis of students' answers in pedagogy, according to I. P. Lvov, showed that most were positive answers, but some students had satisfactory grades, they did not possess good material in pedagogy.

Проаналізовано діяльність чернігівського педагога І. П. Львова, який завідував кафедрою педагогіки з 1952 до 1958 н. р. Опрацьовано звітні матеріали (плани роботи кафедри за 1952, 1953, 1955 н. р., доповідь на резолюцію І. А. Каїрова "О состоянии педагогической науки и мерах ликвидации ее отставания", звіт про проведення державних іспитів та ін.), вказані недоліки й зауваження щодо навчального процесу в освітніх державних установах, які актуальні для сучасного менеджменту в освіті.
УПРАВЛІНСЬКА ДІЯЛЬНІСТЬ І. П. ЛЬВОВА НА ПОСАДІ ЗАВІДУВАЧА КАФЕДРИ ПЕДАГОГІКИ ЧЕРНІГІВСЬКОГО ПЕДАГОГІЧНОГО ІНСТИТУТУ (1952–1958)
Keywords: резолюція; педагог; завідувач кафедри; І. П. Львов.; resolution; lecturer; Head of the Department of Pedagogy; I. P. Lviv.